Corporate strategies for Equitable PCI bank - Villa del Rey, Emma G. (Animo Repository, 2000)
The study is a description and evaluation of the current vision, mission and strategies being used by Equitable PCI Bank as a merged entity. It gives an overview of the banking industry, the mergers and acquisitions in the banking system, the pre-merger profiles of PCI Bank and Equitable Bank respectively, and the profile of the merged bank and its financial performance. To be a dominant domestic player in all major business lines and be a world class financial services provider, the following strategies were used: 1) meet customers' needs through an expanded network 2) achieve leadership in the middle market 3) provide superior customer service 4) intensify e-banking campaign 5) increase effectively for diversity and returns 6) redeploy and retain employees to maximize potentials. In evaluating the company's current strategy, the framework provided by Michel Roberts in the book Strategy Pure and Simple was used. The current strategic drives of the bank are the product/service concept-driven strategy, the distribution method-driven strategy and the market type-driven strategy. To ensure the success of the merger, it is recommended that the bank effect improvements on the following: 1) sharing of the vision 2) determining the profile of the market 3) reviving the relationship banking unit 4) evaluating vital issues on human resources concerns 5) exploring the future challenges in electronic banking. The financial projection shows that Equitable PCI Bank will have cost savings as a result of the integration and income will increase by at least 25% annually.